Literacy in EFL Classroom: In-Service English Teachers’ Perceptions and Practices from Multiliteracies Perspective - Maja, Inke Choirun Nisa’ Il; Nabhan, Salim (JET ADI BUANA, 2022)
The concept of literacy has evolved significantly over the years, with the advent of new technologies and the changing needs of society. In the context of ELT, the study of literacy conceptions and practices is still under-explored. Therefore, this study aims at exploring in-service English teachers’ perceptions and practices of literacy in ELT settings from a multiliteracies perspective. This research used a qualitative case study. The data were taken from in-service English teachers from one of the state high schools in Surabaya, Indonesia through interviews, observation, and document review. The data were then analyzed using thematic analysis. The result indicated that the in-service English teachers perceived a general conception of literacy, a skill-based conception of literacy, and literacy as social practice. In general, the English teachers lacked an understanding of the concept of literacy comprehensively and they associated literacy with skills. In addition, concerning literacy practices from a multiliteracy perspective covered the integration of multimodal in the use of media, the use of technology in teaching and learning activities, and a variety of literacy instructions. Despite some difficulties, the teachers utilized multiple modes of media and technology. This study might have implications for the understanding of the conception of literacy and teaching practices in an EFL setting.